(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Purpose of investigation: The most fundamental part of maintaining reproductive health of women of childbearing age is to treat and improve the health of future mothers, that is, girls, from a young age. Ensuring the implementation of the decision of the Cabinet of Ministers of the Republic of Uzbekistan No. 352 of May 10, 2018 “On measures to increase the efficiency of obstetric-gynecological and medical care services provided to girls and women of childbearing age” (1,2). Expected result: As a result of improving the health of girls from a young age, it is possible to achieve the birth of healthy children from healthy mothers.